RASULULLAH SEBAGAI ROLE MODEL DALAM PENDIDIKAN : INSPIRASI PENDIDIKAN KARAKTER BAGI GENERASI MUDA KAJIAN TERHADAP SURAT AL-AHZAB AYAT 21 - Achmad Alfaridzih; Redy Eka Yudesthira; Nuriyatul Qomariyah; M. Darul Ulum; Lailatun Nurul Maulidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In character education, the role of role models is crucial, considering that various theories on character formation and value instillation consistently place individuals as role models. However, the problem often encountered is the absence or disappearance of role models who can serve as role models in educating the character of the younger generation. Therefore, this study aims to find a solution to this phenomenon by exploring how the Prophet Muhammad (peace be upon him) can serve as a role model in education to inspire the character education of the younger generation, complementing thematic studies aligned with the content of Surah Al-Ahzab, verse 21. This study employed qualitative research with a library research method. The results of this study conclude that the Prophet Muhammad's personality and morals can serve as prime examples in character education. Furthermore, his consistency between his words and actions, inclusiveness in providing understanding and communication patterns, balanced learning objectives with a holistic approach, providing trust as a space for growth, providing motivation, and providing a supportive environment for the educational process.